การพัฒนากลยุทธ์การแข่งขันผลิตภัณฑ์ OTOP หมูฝอยกรอบโกเนียร ตำบลหนองกระโดน อำเภอเมืองนครสวรรค์ จังหวัดนครสวรรค์ - ดาราเรือง กฤษณะ (Modern Management Frontier Journal, 2017)
This study aimed to investigate operating conditions and to develop the competitive strategy of OTOP Product: Konean Shredded Pork at Nongradone Subdistrict, Muang District, Nakhonsawan. Qualitative research was used in this study. The research instrument, in-depth interview from entrepreneurs, was used to collect the data which were analyzed by PRIMO-F model in the part of the context within an organization. PEST Analysis, SWOT Analysis, Nice Cell Matrix were used in the external environment of business. TOWS Matrix technique was used in the operation of strategic planning, and Balances Scorecard was used in determining a measure of the success of the implementation of new strategies. The results of this study found that SO Strategy were 1) to participate in the trade show with the government agencies continuously 2) to increase the distribution channels in tourist attraction, souvenir shops, and e-commerce, and 3) to seek a business co-operation networks both domestic and abroad. WO Strategy were 1) to create a network with the educational institutions or the government agencies to develop the knowledge of management and marketing 2) to develop the logo and packaging. ST Strategy were 1) to study the needs consumer behavior 2) to develop new product in order to make a difference from the competitors. WT Strategy was to develop a technology to increase a efficiency in manufacturing process with eight indicators that had a measure of the success in the strategy implementation.